THE VERIFICATION OF THE HUMOUR DEVELOPMENT AS A LUDIC COMPETENCE MODEL - Kobzieva, Iuliia (PSYCHOLOGICAL JOURNAL, 2020)
The article is focused on the verification of the humour development as a ludic competence model based on its designed implementation programme. Besides, the model is tested in terms of its functional effectiveness. On the summative assessment stage, the model introduction envisaged the ludic competence training. The programme further envisaged a gradual introduction of a designed set of actions during the academic year. The set of actions aimed at “A Real Humorist” ludic position behavioural pattern acquisition. The five actions of the programme got their respective names: 1) “a seven-stage strategy of solving interpersonal and intrapersonal conflicts”; 2) “the specificity of humour as a component of ludic competence; 3) “a five-stage self-assistance model”; 4) “personality identity”; 5) “integration”. The experimental group was diagnosed after each set of actions to reveal if “A Real Humorist” behavioural pattern acquisition was successful. The assessment was based both on the overall changes in the ludic competence development and humour development in accordance with the defined indices. The control stage of the experiment launched after the model testing. This stage involved diagnostic, processing, and analysis of the data. The results of formative assessment reveal qualitative shifts in the experimental group based on 6 out of 8 markers of ludic competence (differences between results of the second testing of the experimental and control groups), and all markers of the assessed shifts in the experimental group. These outcomes prove the effectiveness of the ludic competence training. The main statistically significant indices have increased. Among them are “self-enhancing humour” (р ≤ .01); “self-acceptance” (р ≤ .01); “human as an open system” (р ≤ .05); those containing a psychological meaning of ludic competence: “sensitivity” (р ≤ .05); “humour” (р ≤ .01); “lightness” (р ≤ .05); “imagination” (р ≤ .05); “flirting” (р ≤ .01); «пустотливість» (р ≤ .01); «fugue» (р ≤ .01); “general playfulness» (р ≤ .01); «affiliative humour» (р ≤ .05). Also, indices of actual abilities including “fairness, truth” (р ≤ .05), “love” (p ≤ .05) have grown. The results of the empirical research allowed elaborating a psychological and psycholinguistic structure of humour as a component of ludic competence by defining its elements that correspond to different stages of its development and concluding that the suggested model of humour development is robust in terms of forming of its main components.